2007
DOI: 10.1128/cvi.00320-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Anaplasma phagocytophilum Major Surface Protein 5 and the Extent of Its Cross-Reactivity with A. marginale

Abstract: Major surface protein 5 (Msp5) of Anaplasma marginale is highly conserved in the genus Anaplasma and the antigen used in a commercially available competitive enzyme-linked immunosorbent assay (cELISA) for serologic identification of cattle with anaplasmosis. This study analyzes the degrees of conservation of Msp5 among various isolates of Anaplasma phagocytophilum and the extent of serologic cross-reactivity between recombinant Msp5 (rMsp5) of Anaplasma marginale and A. phagocytophilum. The msp5 genes from var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
39
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 43 publications
0
39
0
4
Order By: Relevance
“…têm possibilitado o desenvolvimento de ensaios de imunoadsorção enzimática (ELISA), baseados em proteínas recombinantes de A. marginale (ARAÚJO et al, 2005), dentre as quais MSP5 (SILVA et al, 2006). Essas pesquisas têm oferecido também uma grande gama de informações sobre a conservação dessas proteínas no gênero (DREHER et al, 2005;STRIK et al, 2007), inclusive com reações sorológicas cruzadas descritas entre MSP5 de A. marginale, A. centrale, A. phagocytophilum e A. ovis (DREHER et al, 2005), e entre MSP5 de A. phagocytophilum e A. platys, Ehrlichia canis e E. chaffeensis (STRIK et al, 2007).…”
unclassified
See 1 more Smart Citation
“…têm possibilitado o desenvolvimento de ensaios de imunoadsorção enzimática (ELISA), baseados em proteínas recombinantes de A. marginale (ARAÚJO et al, 2005), dentre as quais MSP5 (SILVA et al, 2006). Essas pesquisas têm oferecido também uma grande gama de informações sobre a conservação dessas proteínas no gênero (DREHER et al, 2005;STRIK et al, 2007), inclusive com reações sorológicas cruzadas descritas entre MSP5 de A. marginale, A. centrale, A. phagocytophilum e A. ovis (DREHER et al, 2005), e entre MSP5 de A. phagocytophilum e A. platys, Ehrlichia canis e E. chaffeensis (STRIK et al, 2007).…”
unclassified
“…ou Ehrlichia sp., principalmente se utilizados para animais passíveis de infecção por mais de uma espécie (DREHER et al, 2005). No entanto, representam importantes ferramentas de triagem para detecção das infecções por Anaplasma/Ehrlichia em diversos hospedeiros (STRIK et al, 2007).…”
unclassified
“…6 In another study, cross-reactivity was not demonstrated between human or dog antibodies to A. phagocytophilum and the recombinant MSP5 antigen of A. marginale when tested by cELISA. 25 However, cross-reactivity was evident when recombinant MSP5 antigens of A. phagocytophilum or A. marginale were incubated with heterologous sera using an indirect ELISA format. 25 A newly described Ehrlichia genotype (BOV2010) was recently detected in naturally infected cattle from British Columbia, Canada.…”
Section: Introductionmentioning
confidence: 99%
“…25 However, cross-reactivity was evident when recombinant MSP5 antigens of A. phagocytophilum or A. marginale were incubated with heterologous sera using an indirect ELISA format. 25 A newly described Ehrlichia genotype (BOV2010) was recently detected in naturally infected cattle from British Columbia, Canada. 8 Based on the results of cELISA, a the cattle were originally suspected of being infected with A. marginale.…”
Section: Introductionmentioning
confidence: 99%
“…As well as being infected by A. marginale, the cervids are also infected with Anaplasma phagocitophylum (DUMLER et al, 2001) and Anaplasma ovis (HAIGH et al, 2008), which makes it difficult to implement a surveillance by serology. The current serological tests display crossed reactions, even when antigenic sub-units such as MSP5 recombinant protein are employed as antigens, because Anaplasma species have similar B epitopes (STRIK et al, 2007).…”
Section: Introductionmentioning
confidence: 99%